Discovery and Biosynthesis of Bolagladins: Unusual Lipodepsipeptides from Burkholderia gladioli Clinical Isolates. (23rd September 2020) - Dashti, Yousef; Nakou, Ioanna T.; Mullins, Alex J.; Webster, Gordon; Jian, Xinyun; Mahenthiralingam, Eshwar; Challis, Gregory L.
Abstract: Two Burkholderia gladioli strains isolated from the lungs of cystic fibrosis patients were found to produce unusual lipodepsipeptides containing a unique citrate‐derived fatty acid and a rare dehydro‐β‐alanine residue. The gene cluster responsible for their biosynthesis was identified by bioinformatics and insertional mutagenesis. In‐frame deletions and enzyme activity assays were used to investigate the functions of several proteins encoded by the biosynthetic gene cluster, which was found in the genomes of about 45 % of B. gladioli isolates, suggesting that its metabolic products play an important role in the growth and/or survival of the species. The Chrome Azurol S assay indicated that these metabolites bind ferric iron, which suppresses their production when added to the growth medium. Moreover, a gene encoding a TonB‐dependent ferric‐siderophore receptor is adjacent to the biosynthetic genes, suggesting that these metabolites may function as siderophores in B. gladioli . Abstract : Bolagladins A and B were discovered as products of a cryptic nonribosomal peptide synthetase in two Burkholderia gladioli strains isolated from the lungs of cystic fibrosis patients. These metabolites contain a unique citrate‐primed fatty acid and a rare dehydro‐β‐alanine residue. A combination of bioinformatics analysis and genetic and biochemical experiments illuminated the mechanisms for the installation of these unusual structural features.